TINJAUAN KOREOGRAFI TARI MANGKIK SATAIH DI DINAS KEBUDAYAAN DAN PARIWISATA KOTA SUNGAI PENUH PROVINDI JAMBI - Lara Sintia; Herlinda Mansyur; Afifah Asriati (FBS Universitas Negeri Padang, 2018)
AbstractThis article aimed to describe and explain the choreography of Mangkik Staih Dance in Sungai Penuh Tourism Culture Office, Jambi Province. The type of this research was qualitative using descriptive method. The object of this research was Mangkik Staih dance. The techniques of data collection were literature study, observation, interviews, and documentation. The techniques of data analysis were conducted by selecting the data that were considered important, compiling the selected data, analyzing the data with interpretation techniques. The results of this study indicated that the Mangkik Staih dance was a creation dance which was the development of the Asik dance which functioned as entertainment. the choreography of Mangkik Staih dance was in the form of a large group dance, the musical instruments used were tambourine, keyboard, car, bass, drum, costume that were used by Kerinci Traditional, Plate Property, Small Bowls Contain Seven Variety Flowers, Large Bowls Contain Rice and Sirih, Light Torch from Coconut, Bamboo, Broken Dishes, Stoves and Cauldrons. Keywords: Assessment, Choreographer, Staih Mangkung Dance